Design and Development of an IoT-Based Car Security System Integrating GPS, Piezoelectric Sensors, and Glass Break Sensors - Rohdyawan, Zaidan Wafi; Hakim, M. Iman Nur (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
The increasing number of motor vehicles has been accompanied by a rise in vehicle-related crimes, highlighting the need for more advanced and adaptive security systems. Conventional vehicle security systems are limited by their inability to provide real-time monitoring and accurate intrusion detection. This study aims to develop and evaluate an Internet of Things (IoT)-based vehicle security system that integrates multiple sensors to improve detection accuracy and responsiveness. The research employs a Research and Development (R&D) Level 3 approach, involving system design, development, and performance testing. The proposed system utilizes a combination of piezoelectric sensors for vibration detection, glass break sensors for acoustic detection, and a GPS module for real-time tracking, all controlled by an ESP32 microcontroller and connected to a Telegram-based notification system. The results indicate that the multi-sensor integration enhances the system’s ability to detect various intrusion patterns more accurately while minimizing false alarms compared to single-sensor systems. Additionally, real-time notifications and location tracking improve user responsiveness to potential threats. In conclusion, the developed system provides a more effective, accurate, and adaptive vehicle security solution suitable for modern security challenges.